2020
DOI: 10.1155/2020/8881901
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Hydraulic Fracture Extension Based on the Meshless Method

Abstract: The fracture propagation in hydraulic fracturing is described as a nonlinear problem dynamic boundary. Due to the limitation of mesh refinement, it is difficult to obtain the real crack propagation path using conventional numerical methods. Meshless methods (MMs) are an effective method to eliminate the dependence on the computational grid in the simulation of fracture propagation. In this paper, a hydraulic fracture propagation model is established based on the element-free Galerkin (EFG) method by introducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Owing to the requirements of oil and gas reservoirs and field technology, simulations of hydraulic fracturing have been rapidly developed, with great advances both in theory and laboratory experiments. In virtue of developments in computer technology and numerical calculation method, models for hydraulic fracture propagation have evolved from analytical models (KGD model, 1,2 PKN model, 3 pseudo‐3D model 4 ), semi‐analytical models (liner network model, 5,6 UFM model 7,8 ) to numerical models (classical finite element method, 9–11 displacement discontinuous method, 12–14 discrete element methods, 15,16 extended finite element method 17–20 ), and the theory has evolved from double‐wing seam theory to multi‐factor theory, which considers the effects of natural fracture, 21–24 stress shadow, 25,26 hydro‐mechanical coupling, 27–29 thermal strain 30,31 . Despite great achievements in numerical simulations of hydraulic fracture propagation, most studies of hydraulic fracture propagation models are based on homogeneous media., It was found that the propagation direction of dry crack may deviate from the direction of maximum horizontal principal stress as a result of the anisotropy of rocks 32–36 .…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the requirements of oil and gas reservoirs and field technology, simulations of hydraulic fracturing have been rapidly developed, with great advances both in theory and laboratory experiments. In virtue of developments in computer technology and numerical calculation method, models for hydraulic fracture propagation have evolved from analytical models (KGD model, 1,2 PKN model, 3 pseudo‐3D model 4 ), semi‐analytical models (liner network model, 5,6 UFM model 7,8 ) to numerical models (classical finite element method, 9–11 displacement discontinuous method, 12–14 discrete element methods, 15,16 extended finite element method 17–20 ), and the theory has evolved from double‐wing seam theory to multi‐factor theory, which considers the effects of natural fracture, 21–24 stress shadow, 25,26 hydro‐mechanical coupling, 27–29 thermal strain 30,31 . Despite great achievements in numerical simulations of hydraulic fracture propagation, most studies of hydraulic fracture propagation models are based on homogeneous media., It was found that the propagation direction of dry crack may deviate from the direction of maximum horizontal principal stress as a result of the anisotropy of rocks 32–36 .…”
Section: Introductionmentioning
confidence: 99%